Acute toxicity effects of 2,4-D herbicide on common carp(Cyprinus carpio Linnaeus, 1758 ) and grass carp (Ctenopharyngodon idella valenciennes,1844) - Z. Al-Swefee, Duha; M. Al-Azawi, Ahmed J. (Iraqi Journal of Science, 2023)
The acute toxicity effects of (2,4-D) pesticide to the common carp and grass carp was determined through 24, 48, 72 and 96 hr. Group of eight Common carp (Cyprinus carpio L., 1758; Pisces, Cyprinidae) and group of eight of grass carp (Ctenopharyngodon idella) were exposed to the 2,4-d. Lethal concentration (LC50) was determined with probit analysis. The median lethal concentration (LC50) values for common and grass carp were (157.77, 157.25, 156.41 and 152.62) and (115.92, 114.92, 112.94 and 96.52) respectively. Behavioral changes of the above mentioned species were examined for various herbicide concentrations.